Foreign Direct Investment Negotiations on the Domestic Component Level Framework: Technology Diplomacy between Indonesia and Apple Inc. - Delima, Yuliana Puti; Sinambela, Stivani (Universitas Cenderawasih, 2026)
Technology diplomacy has emerged as a strategic instrument for developing countries seeking to enhance their bargaining position vis-à-vis global technology firms. This article examines the negotiation dynamics between the Indonesian government and Apple Inc. concerning the implementation of a 40% Domestic Component Level (TKDN) requirement during the 2020-2024 period. Based on the Foreign Direct Investment (FDI) Bargaining Model and a critical political economy approach, this study analyzes government policy documents, official corporate statements, and national and international media reports to trace the bargaining process and its outcomes. The findings reveal that having formal regulatory authority did not necessarily provide Indonesia with effective leverage in negotiations. Despite Indonesia’s large market size and formal control over local content certification, structural constraints in industrial capacity, supply chain integration, and institutional coordination limited the credibility of regulatory pressure. KEYWORDSAsymmetry; Foreign Direct Investment; Global Value Chain; Indonesia; Technology Diplomacy